Long-platform sodium storage molecular sieve hard carbon negative electrode material and preparation method and application thereof

By ball milling, acid washing, alkaline washing and high-temperature carbonization treatment of carbon molecular sieves, a hard carbon negative electrode material with a long voltage platform was prepared, which solved the problem of low reversible specific capacity of sodium ion battery negative electrode materials and achieved sodium ion battery performance with high capacity and long cycle life.

CN120646810APending Publication Date: 2025-09-16龙子湖新能源实验室 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510955454.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

The existing hard carbon negative electrode materials for sodium ion batteries have a low reversible specific capacity in the low potential platform region, which limits the improvement of the energy density of sodium ion batteries.

Method used

By ball milling, acid washing, alkaline washing and high-temperature carbonization treatment of carbon molecular sieves, a hard carbon negative electrode material with a long voltage platform was prepared, and its pore structure and nanopore opening rate were regulated to improve the ion diffusion kinetics performance.

Benefits of technology

The prepared long platform sodium storage molecular sieve hard carbon negative electrode material has a high specific surface area and excellent ion diffusion kinetics, providing higher reversible specific capacity and longer cycle life, and is suitable for high-capacity sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120646810A_ABST
    Figure CN120646810A_ABST
Patent Text Reader

Abstract

The invention provides a long-platform sodium-storage molecular sieve hard carbon negative electrode material as well as a preparation method and application thereof, belongs to the technical field of sodium-ion batteries, and aims at solving the technical problems of low reversible specific capacity and low low-potential platform of a sodium-ion battery negative electrode material. According to the invention, a typical carbon molecular sieve is used as a raw material, a micropore / mesopore graded pore structure is regulated and controlled through ball milling, acid washing, alkali washing and high-temperature carbonization processes, and an ordered pore channel system of which the pore diameter is adaptive to sodium ions is formed. The material has a high pore volume (0.1-0.3 cm < 3 > / g), a short-range ordered carbon layer and a rich nanopore structure, and the platform capacity ratio and the ion diffusion dynamic performance are remarkably improved. By optimizing the carbonization temperature (such as 1600 DEG C) and selection, the material shows high reversible specific capacity (gt; 200mAh / g), and is suitable for sodium ion batteries with high energy density and long cycle life. An embodiment test shows that the charge-discharge reversible specific capacity and the cycling stability of the material are obviously superior to those of a traditional hard carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a negative electrode hard carbon material. Background Art

[0002] Lithium-ion batteries are becoming an increasingly important energy storage solution for new energy vehicles and portable electronic devices due to their significantly high energy density and excellent long cycle life. However, the scarcity and uneven distribution of lithium resources limit the further large-scale application of lithium-ion batteries. Fortunately, sodium resources are abundant and low-cost, and sodium-ion batteries are considered to be one of the most competitive sustainable technologies for large-scale energy storage systems and smart grids. Although a variety of sodium storage positive electrode materials have been developed, such as layered oxides, polyanionic compounds and Prussian blue, the pursuit of high-performance anode materials with high specific capacity and cost-effectiveness remains a major challenge in the development of sodium-ion batteries and has become an important key factor in improving their energy density.

[0003] For example, patent publication number CN 116750747A discloses a hard carbon negative electrode material for sodium ion secondary batteries and a preparation method thereof. The hard carbon material for sodium ion batteries is made of poisoned and failed carbon molecular sieves, which are mechanically crushed, purified by low-temperature acid washing, and then heat-treated under inert atmosphere protection. The prepared hard carbon negative electrode material for sodium ion batteries has a nano-scale microporous structure and is in the form of irregular micron-sized particles in its macroscopic state, exhibiting good electrochemical properties.

[0004] However, to date, most high-performance hard carbon anodes for sodium-ion batteries generally exhibit similar charge and discharge behaviors, with two distinct regions: a slope region above 0.1V and a platform region below 0.1V. Generally, the platform region exhibits a higher capacity than the slope region, significantly improving the reversible specific capacity. In addition, the low-potential platform can increase the open-circuit voltage of the full cell to a certain extent, further improving the energy density of sodium-ion battery devices. Therefore, the design and analysis of hard carbon anodes with a high proportion of platform capacity plays an important role in increasing the energy density of sodium-ion batteries. Summary of the Invention

[0005] In response to the technical problems of low reversible specific capacity and low low-potential platform of sodium-ion battery negative electrode materials, the present invention proposes a long-platform sodium-storage molecular sieve hard carbon negative electrode material and its preparation method and application. The prepared long-platform sodium-storage molecular sieve hard carbon negative electrode material has a long voltage platform sodium storage characteristic and is suitable for sodium-ion batteries with high capacity and long cycle life.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A long platform sodium storage molecular sieve hard carbon negative electrode material, the preparation method comprising the following steps:

[0008] (1) Ball milling: ball milling the carbon molecular sieve;

[0009] (2) Pickling: Add the milled carbon molecular sieve into acid solution;

[0010] (3) alkali washing: adding the acid-washed carbon molecular sieve into alkali solution for alkali washing;

[0011] (4) High-temperature carbonization: The carbon molecular sieve after alkali washing is calcined to obtain a long platform sodium storage molecular sieve hard carbon negative electrode material.

[0012] The process parameters of the ball milling are: the mass ratio of grinding medium to material is 20:1-2, the total effective time of ball milling is 12-24 hours, and the operation is intermittent.

[0013] The acid in the acid solution is HCl, and the concentration of the acid solution is 0.1-3 mol / L. It is used to remove metal salt impurities.

[0014] The pickling temperature is room temperature and the pickling time is 0.5-2h.

[0015] The alkali in the alkali solution is KOH, and the concentration of the alkali solution is 0.1-3 mol / L. It is used to increase the opening rate and pore volume of hard carbon-sealed nanopores.

[0016] The temperature of the alkali washing is 70-90° C., and the time is 0.5-2 h.

[0017] The calcination temperature is 1100° C.-2600° C., and the calcination time is 1-5 hours.

[0018] A long platform sodium storage molecular sieve hard carbon negative electrode material is used in sodium ion batteries.

[0019] Beneficial effects of the present invention: The long platform sodium storage molecular sieve hard carbon negative electrode material of the present invention has a high specific surface area and a controllable pore size structure. The carbon molecular sieve has a highly ordered microporous / mesoporous structure (usually pore size <2nm), and its specific surface area can reach 1000-3000m 2 / g, far exceeding traditional hard carbon. This structure can precisely adapt to the size of sodium ions by regulating the pore size distribution, providing more active sites, thereby providing a long platform capacity. At the same time, carbon molecular sieve negative electrode materials have excellent ion diffusion kinetics advantages: short-range ordered carbon layers and open pores shorten the Na + Diffusion path, reducing the diffusion barrier. Its ionic conductivity can reach 10 -3 S / cm, better than disordered hard carbon (10 -4 S / cm). Finally, the preparation method of the negative electrode material of the present invention has the advantages of being safe, simple and easy to be produced and applied on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 This is the adsorption-desorption test analysis curve of molecular sieve.

[0022] Figure 2 This is the TEM image of the carbon molecular sieve of Example 5.

[0023] Figure 3 This is the TEM image of the carbon molecular sieve of Example 6.

[0024] Figure 4 This is the charge and discharge curve of the first cycle of Example 5.

[0025] Figure 5 This is a comparison chart of platform capacity between Example 5 and other examples. DETAILED DESCRIPTION

[0026] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0029] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0030] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0031] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0032] S4. Alkaline washing: The sample obtained in step S3 was added to a 2 mol / L KOH solution and stirred at 80°C for 1 h;

[0033] S5. Carbonization: In an argon atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min and then to 1100°C at a heating rate of 2°C / min. The clean carbon molecular sieve obtained in step S4 was calcined for 2 h to obtain a carbonized product.

[0034] Example 2

[0035] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0036] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0037] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0038] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0039] S4. Alkaline washing: The sample obtained in step S3 was added to a 2 mol / L KOH solution and stirred at 80°C for 1 h;

[0040] S5. Carbonization: In an argon atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min and then to 1300°C at a heating rate of 2°C / min. The clean carbon molecular sieve obtained in step S4 was calcined for 2 h to obtain a carbonized product.

[0041] Example 3

[0042] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0043] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0044] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0045] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0046] S4. Alkaline washing: The sample obtained in step S3 was added to a 2 mol / L KOH solution and stirred at 80°C for 1 h;

[0047] S5. Carbonization: In an argon atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min and then to 1400°C at a heating rate of 2°C / min. The clean carbon molecular sieve obtained in step S4 was calcined for 2 h to obtain a carbonized product.

[0048] Example 4

[0049] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0050] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0051] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0052] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0053] S4. Alkaline washing: The sample obtained in step S3 was added to a 2 mol / L KOH solution and stirred at 80°C for 1 h;

[0054] S5. Carbonization: In an argon atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min and then to 1500°C at a heating rate of 2°C / min. The clean carbon molecular sieve obtained in step S4 was calcined for 2 h to obtain a carbonized product.

[0055] Example 5

[0056] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0057] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0058] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0059] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0060] S4. Alkaline washing: The sample obtained in step S3 was added to a 2 mol / L KOH solution and stirred at 80°C for 1 h;

[0061] S5. Carbonization: In an argon atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min and then to 1600°C at a heating rate of 2°C / min. The clean carbon molecular sieve obtained in step S4 was calcined for 2 h to obtain a carbonized product.

[0062] Example 6

[0063] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0064] S1. Ball milling: The carbon molecular sieve is milled in a planetary ball mill at an autorotation speed of 500 r / min and an orbital speed of 15 r / min.

[0065] The mass ratio of grinding media to material is 20:1, the mass ratio of large balls (Φ12 mm) to small balls (Φ3 mm) is 4:1, and the carbon molecular sieve raw material (15 g) and grinding media (240 g large balls + 60 g small balls) are loaded in proportion for ball milling. The mill is operated intermittently, and the mill is stopped for cooling for 10 minutes every 4 hours of milling. The total effective time is 16 hours;

[0066] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0067] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0068] S4. Alkaline washing: The sample obtained in step S3 was added to a 2 mol / L KOH solution and stirred at 80°C for 1 h;

[0069] S5. Carbonization: In an argon atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min and then to 2600°C at a heating rate of 2°C / min. The clean carbon molecular sieve obtained in step S4 was calcined for 2 h to obtain a carbonized product.

[0070] Comparative Example 1

[0071] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0072] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0073] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0074] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0075] S4 carbonization: in an argon atmosphere at a heating rate of 5 ° C / min to 1000 ° C and then at a heating rate of 2 ° C / min to 1300 ° C the clean carbon molecular sieve obtained in step S3 was calcined for 2h to obtain a carbonized product after calcination;

[0076] Comparative Example 1 was not subjected to alkali washing, and other conditions were the same as those in Example 2.

[0077] Comparative Example 2

[0078] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0079] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0080] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0081] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0082] S4 carbonization: in an argon atmosphere at a heating rate of 5 ° C / min to 1000 ° C and then at a heating rate of 2 ° C / min to 1400 ° C the clean carbon molecular sieve obtained in step S3 was calcined for 2h to obtain a carbonized product after calcination;

[0083] Comparative Example 2 was not subjected to alkali washing, and other conditions were the same as those in Example 3.

[0084] Comparative Example 3

[0085] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0086] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0087] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0088] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0089] S4 carbonization: in an argon atmosphere at a heating rate of 5 ° C / min to 1000 ° C and then at a heating rate of 2 ° C / min to 1500 ° C the clean carbon molecular sieve obtained in step S3 was calcined for 2h to obtain a carbonized product after calcination;

[0090] Comparative Example 3 did not undergo alkali washing, and other conditions were the same as those of Example 4.

[0091] Comparative Example 4

[0092] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0093] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0094] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0095] S3 acid washing: to the sample obtained in step S2, 2mol / LHCl was added and stirred at room temperature for 1h to remove impurities;

[0096] S4 carbonization: in an argon atmosphere at a heating rate of 5 ° C / min to 1000 ° C and then at a heating rate of 2 ° C / min to 1600 ° C the clean carbon molecular sieve obtained in step S3 was calcined for 2h to obtain a carbonized product after calcination;

[0097] Comparative Example 4 was not subjected to alkali washing, and other conditions were the same as those in Example 5.

[0098] Application Examples

[0099] like Figure 1 As shown, the molecular sieve has a specific surface area of ​​up to 1700m 2 / g, and the pore sizes are concentrated in the range below 2nm, which are typical ultra-micropores. Figure 2 and 3It was found that the molecular sieve showed different interlayer spacings in different treatment processes, which had a significant impact on the sodium storage dynamics. The carbon molecular sieve hard carbon materials prepared in Examples 1-5 and Comparative Examples 1-4 were used as negative electrode materials for sodium ion batteries, and half-cells were assembled for testing. The hard carbon materials in the above examples were slurried according to the ratio of hard carbon material: polyvinylidene fluoride (PVDF): conductive carbon black (Super-p) = 8:1:1 (weight ratio), and the slurry was adjusted with NMP, coated on Cu foil and dried in a vacuum drying oven for 12 hours to make a pole piece. Glass fiber GF-A was used as a diaphragm, and a metal sodium sheet was used as a reference electrode and a counter electrode. Commercially available sodium ion electrolyte was used to assemble CR2025 button batteries in an argon atmosphere. The charge and discharge voltage range was 0-2.0V, and the charge and discharge test was carried out at a current density of 50mA / g in the first week. The reversible specific capacity and capacity share of the low potential platform are shown in Table 1. Figure 4 and 5 It was concluded that Example 5 had the highest platform specific capacity, and accounted for 69% of the total capacity, indicating its excellent kinetic performance at the low potential platform.

[0100] Table 1 Performance test table of sodium ion button batteries assembled in the embodiment and comparative example

[0101]

[0102] Example 7

[0103] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0104] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 h, with a total effective time of 16 hours.

[0105] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0106] S3 acid washing: to the sample obtained in step S2 was added 1mol / LHCl and stirred at room temperature for 2h to remove impurities;

[0107] S4. Alkaline washing: The sample obtained in step S3 was added to a 3 mol / L KOH solution and stirred at 90°C for 0.5h;

[0108] S5. Carbonization: In an argon atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min and then to 1100°C at a heating rate of 2°C / min. The clean carbon molecular sieve obtained in step S4 was calcined for 5 hours to obtain a carbonized product.

[0109] Example 8

[0110] A method for preparing a molecular sieve hard carbon material comprises the following steps:

[0111] S1. Ball milling: The carbon molecular sieve was milled in a planetary ball mill at an autogenous speed of 500 r / min and an orbital speed of 15 r / min, a grinding medium to material mass ratio of 20:1, a large ball (Φ12 mm) to a small ball (Φ3 mm) mass ratio of 4:1, and the carbon molecular sieve raw material (15 g) and the grinding medium (240 g large ball + 60 g small ball) were loaded in proportion for ball milling. The milling was performed intermittently, and the milling was stopped for 10 minutes to cool for 4 hours, with a total effective time of 24 hours.

[0112] S2 sieving: The sample obtained in step S1 was sieved and sieved with a 100-mesh sieve to ensure that the particle size was less than 150um;

[0113] S3 acid wash: to the sample obtained in step S2 was added 3mol / LHCl and stirred at room temperature for 0.5h to remove impurities;

[0114] S4. Alkaline washing: The sample obtained in step S3 was added to a 1 mol / L KOH solution and stirred at 70°C for 2h;

[0115] S5. Carbonization: In an argon atmosphere, the temperature was raised to 1000°C at a heating rate of 5°C / min and then to 1100°C at a heating rate of 2°C / min. The clean carbon molecular sieve obtained in step S4 was calcined for 1 h to obtain a carbonized product.

[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a long platform sodium storage molecular sieve hard carbon negative electrode material, characterized in that: The following steps are involved: (1) Ball milling: ball milling the carbon molecular sieve; (2) Pickling: Add the milled carbon molecular sieve into acid solution; (3) alkali washing: adding the acid-washed carbon molecular sieve into alkali solution for alkali washing; (4) High-temperature carbonization: The carbon molecular sieve after alkali washing is calcined to obtain a long platform sodium storage molecular sieve hard carbon negative electrode material.

2. The method for preparing the long platform sodium storage molecular sieve hard carbon negative electrode material according to claim 1, characterized in that: The process parameters of the ball milling are: the mass ratio of grinding medium to material is 20:1-2, the total effective time of ball milling is 12-24 hours, and the operation is intermittent.

3. The method for preparing the long platform sodium storage molecular sieve hard carbon negative electrode material according to claim 1, characterized in that: The acid in the acid solution is HCl; the concentration of the acid solution is 0.1-3 mol / L.

4. The method for preparing the long platform sodium storage molecular sieve hard carbon negative electrode material according to claim 3, characterized in that: The pickling temperature is room temperature and the pickling time is 0.5-2h.

5. The method for preparing the long platform sodium storage molecular sieve hard carbon negative electrode material according to claim 1, characterized in that: The alkali in the alkali solution is KOH.

6. The method for preparing the long platform sodium storage molecular sieve hard carbon negative electrode material according to claim 5, characterized in that: The concentration of the alkali solution is 0.1-3 mol / L.

7. The method for preparing the long platform sodium storage molecular sieve hard carbon negative electrode material according to claim 6, characterized in that: The temperature of the alkali washing is 70-90° C., and the time is 0.5-2 h.

8. The method for preparing the long platform sodium storage molecular sieve hard carbon negative electrode material according to any one of claims 1 to 7, characterized in that: The calcination temperature is 1100° C.-2600° C., and the calcination time is 1-5 hours.

9. A long platform sodium storage molecular sieve hard carbon negative electrode material prepared by the method according to any one of claims 1 to 8.

10. Use of the long platform sodium storage molecular sieve hard carbon negative electrode material according to claim 9 in sodium ion batteries.

Citation Information

Patent Citations

  • Hard carbon negative electrode material for sodium ion secondary battery and preparation method of hard carbon negative electrode material

    CN116750747A